Understanding and Improving Mechanical Properties in 3D printed Parts Using a Dual‐Cure Acrylate‐Based Resin for Stereolithography. Issue 12 (20th September 2018) - Uzcategui, Asais Camila; Muralidharan, Archish; Ferguson, Virginia L.; Bryant, Stephanie J.; McLeod, Robert R.
Abstract : Application of 3D printed structures via stereolithography (SLA) is limited by imprecise dimensional control and inferior mechanical properties. These challenges is attributed to poor understanding of polymerization behavior during the printing process and inadequate post‐processing methods. The former via a modified version of Jacob's working curve equation that incorporates the resin's sub‐linear response to irradiation intensity is addressed by the authors. This new model provides a more accurate approach to select 3D printing parameters given a desired z ‐resolution and conversion profile along the depth of the printed part. The authors use this improved model to motivate a novel material design that can be post‐processed to be indistinguishable from the polymer at 100% conversion. This approach employs a dual initiating system in which photo‐initiated printing is followed by a thermal post‐cure to achieve uniform conversion. The authors show that this approach enables fast printing times (10 s per layer), exceptional horizontal resolution (1–10 microns), precise control over vertical resolution, and decreased surface corrugations on a 10's of microns scale. The techniques described herein use an acrylate‐based SLA resin, but the approach can be extended to other monomer systems to simultaneously achieve predictable properties and dimensions that are critical for application of additive manufacturing in load‐bearing applications. Abstract : An acrylate based dual‐cure 3D‐printing resin is developed to increase the fidelity and mechanical properties of printed structures. The resin applies a dual initiating system in which photo‐initiated printing is followed by a thermal post‐cure to achieve uniform conversion. The resin design is motivated by a model that provides a more accurate approach to select 3D printing parameters given a desired z ‐resolution.